2011
DOI: 10.1089/adt.2011.0425
|View full text |Cite
|
Sign up to set email alerts
|

hERGCentral: A Large Database to Store, Retrieve, and Analyze Compound-Human Ether-à-go-go Related Gene Channel Interactions to Facilitate Cardiotoxicity Assessment in Drug Development

Abstract: The unintended and often promiscous inhibition of the cardiac human Ether-à-go-go related gene (hERG) potassium channel is a common cause for either delay or removal of therapeutic compounds from development and withdrawal of marketed drugs. The clinical manifestion is prolongation of the duration between QRS complex and T-wave measured by surface electrocardiogram (ECG)-hence Long QT Syndrome. There are several useful online resources documenting hERG inhibition by known drugs and bioactives. However, their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…Using automated electrophysiology, we have conducted a large compound library screen to identify and characterize small molecule modulators for hERG potassium channels (16). Although a vast majority of modulators were inhibitors, a small number of activators have been identified in the primary screen.…”
Section: Resultsmentioning
confidence: 99%
“…Using automated electrophysiology, we have conducted a large compound library screen to identify and characterize small molecule modulators for hERG potassium channels (16). Although a vast majority of modulators were inhibitors, a small number of activators have been identified in the primary screen.…”
Section: Resultsmentioning
confidence: 99%
“…The high hit rate (~27%) demonstrated the promiscuity property of hERG channels by a diverse range of compound structures. The data would provide the information for other users of the MLSMR compound collection to triage compounds in the early stage [20] . Analysis of hERG data further demonstrated that hERG liability compounds tend to be more hydrophobic, high-molecular, flexible and polarizable.…”
Section: Promiscuity Of Herg Inhibition Affected By Physiochemical Prmentioning
confidence: 99%
“…To prioritize the active compounds identified in other screenings based on their hERG liability and generate data to facilitate understanding of mechanisms underlying promiscuity regarding hERG inhibition, we conducted a screening of the (MLSMR) library of approximately 300 000 compounds at both 1 µmol/L and 10 µmol/L using automated electrophysiology. The hERG data are available in the website called hERGCentral (www.hergcentral.org), in which people can retrieve and analyze compound-hERG interaction based on their needs [20] . In additon, earlier we have uploaded part of the hERG screen data to PubChem website [21] and reported some computational prediction analysis for hERG liability [22] .…”
mentioning
confidence: 99%
“…Our present analysis integrates earlier results in which we have independently profiled over 300,000 compounds (including approximately half of the CMap compounds) in the NIH Molecular Library Small Molecule Repository (MLSMR) for their ability to inhibit hERG current in a high-throughput electrophysiological assay [26]. Combining our database with additional publicly available annotations for LQT side effect allowed us to identify clusters of drugs with similar expression profiles in the CMap enriched for channel inhibitors.…”
Section: Introductionmentioning
confidence: 71%
“…To identify higher-level relationships between individual clusters, we further aggregated the data by recursively re-clustering these exemplars to attain a global view of the number of characteristic patterns of drug-induced gene expression changes in this collection. We integrated the gene expression measurements with annotations for hERG inhibition derived from two sources: a previously described dataset of electrophysiology measurements of hERG inhibition ( http://www.hERGcentral.org ) [26], and lists of drugs that have been clinically linked to LQT side effects ( http://ww.sads.org.uk and http://www.qtdrugs.org ). Drugs with records in hERGcentral were annotated as inhibitors if they decreased hERG current by 50% or more at 10 µM concentration, representing an IC 50 value of approximately 10 µM or less.…”
Section: Resultsmentioning
confidence: 99%